Tiger and leopard habitat use in Bhutan revealed by Bayesian multi-scale spatial occupancy models - Singye Wangmo; Marc Kéry; David W. Macdonald; Abishek Harihar; Caroline C. Sartor; Samuel A. Cushman; Patrick Burns; Andrew J.Loveridge; Amy Dickman (Biological Conservation, 2026)

US Immigrants and their Knowledge of their Family History of Cancer: A Population-Based Study - Wendy Sanwu Kutten; Julius Bright Danquah; Naa-Amy K. Wayne; Samuel Anokye-Mensah; Samuel T. Opoku; Bettye A. Apenteng (Journal of Cancer Education, 2026)

We need to talk about maladaptation - Amy Waananen; Samuel P. Reed; Diele Lobo; Patrick I. Hancock; Jessica J. Hellmann (Climatic Change, 2026)
Climate adaptation actions should help, not harm. However, adaptation efforts can backfire, increasing vulnerability to climate change—a phenomenon known as maladaptation. In this essay, we argue that maladaptation dialogues—inclusive and deliberate conversations about negative consequences and failures of adaptation actions, especially among adaptation professionals—offer unique benefits for advancing climate adaptation practice. When approached deliberately, dialogue can promote shared understanding, learning, and inclusive adaptation processes, helping prevent and respond to climate adaptation gone awry. Further, by integrating conversations about maladaptation into the adaptation cycle, we can enhance adaptation efforts, leading to more innovative and resilient adaptation organizations.

Entertainers, not educators? Social media influencers and risk communication in outdoor travel - Samuel Cornell; Timothy Piatkowski; Robert Brander; Amy E. Peden (Journal of Outdoor Recreation and Tourism, 2026)

Genetic Surveillance Reveals Differential Evolutionary Dynamic of Anopheles gambiae Under Contrasting Insecticidal Tools Used in Malaria Control - Harun N. Njoroge; Lilian Namuli; Sanjay C. Nagi; Anastasia Hernandez‐Koutoucheva; Daniel P. McDermott; Erin Knight; Samuel Gonahasa; Amy Lynd; Ambrose Oruni; Catherine Maiteki‐Sebuguzi; Jimmy Opigo; Adoke Yeka; et al. (Molecular Ecology, 2026)
Malaria, a febrile disease caused by the Plasmodium parasites and transmitted by mosquitoes, is a leading cause of mortality in children under 5 in endemic countries. The widespread deployment of insecticide‐treated bed nets (ITNs) has significantly reduced malaria transmission, but rising levels of insecticide resistance threaten to halt the progress. Monitoring insecticide resistance is vital for effective vector control, particularly when deploying new tools. Understanding mosquito population responses to these interventions is crucial for guiding control programmes in making informed decisions about the selection, timing and geographic deployment of tools. This genomic study investigates the demographic and evolutionary consequences on the malaria vector Anopheles gambiae of deploying standard ITNs (containing only pyrethroids) and pyrethroid‐PBO nets (containing pyrethroids plus the synergist piperonyl butoxide) during a clinical trial in Uganda. Despite substantial reductions in indoor mosquito densities in the clinical trial, estimates of nucleotide diversity (π) and linkage disequilibrium revealed no significant decline in effective population size, reflecting continued large population size even after effective control. Marked allele frequency shifts at resistance‐associated loci indicated strong selection pressures driven by the interventions, with distinct selective dynamics between the two net types, highlighting alternative pyrethroid detoxification pathways in the presence of PBO. A duplication in the Cyp9k1 gene significantly increased in frequency in populations exposed to pyrethroid‐only nets but decreased in populations exposed to PBO‐treated nets, suggesting that selection for over‐expression of this gene is removed when this resistance mechanism is impacted by PBO. An alternative potential detoxification mechanism was selected within a region of the 2La chromosomal inversion on chromosome 2 L, which encompasses the UDP‐glucose 6‐dehydrogenase gene. This variant consistently increased in frequency when exposed to PBO‐treated nets. Additionally, pyrethroid‐only nets selected for a novel locus on the X chromosome containing the diacylglycerol kinase gene, which is potentially linked to behavioural adaptations through its role in neurotransmission modulation. Our findings underscore the importance of genomic surveillance in vector control, revealing distinct evolutionary dynamics of insecticide resistance mechanisms in the presence of PBO. While ITNs remain effective, the persistence and evolution of resistance‐associated alleles highlight the need for adaptive and dynamic resistance management strategies. By integrating high‐resolution genomic data with epidemiological and entomological monitoring, this study offers actionable insights to sustain malaria control efforts amid the ongoing challenge of insecticide resistance.

Shared mechanisms in neuromyelitis optica spectrum disorder and spaceflight-associated neuro-ocular syndrome: Insights into central nervous system fluid dynamics, glymphatic function, and astrocyte dysregulation - Phani Paladugu; Rahul Kumar; Kyle Sporn; Joshua Ong; Amy Song; Tejas Sekhar; Chirag Gowda; Nicole Davidoff; Samuel Shin; Andrew G. Lee (Life Sciences in Space Research, 2025)

Chronic sublethal exposure to methylmercury lengthens telomeres in developing zebra finches - Rachel L. Davis; Samuel D. Mason; Christian Wake; Giulia Fabozzi; William L. Catalano; Chaim A. Schramm; Amy R. Henry; Cokie L. Parker; Farida Laboune; Casey L. McLaughlin; Jeffrey D. Kittilson; John P. Swaddle; et al. (Environmental Pollution, 2025)

Addressing Food Insecurity in University Students: Barriers and Tailored Solutions for On- and Off-Campus Meal Access - Julia Gaiser; Anna Barbosa; Molly Waring; Amy Egbert; Samuel Nunes; Sydney Hodges; Valerie Duffy (Journal of Nutrition Education and Behavior, 2025)

Reduced GIRK expression in midbrain dopamine neurons during prolonged abstinence from fentanyl self-administration - Narges Pachenari; Amy L. Channell; Andrew J. Belilos; Samuel J. Dienel; Khaled Moussawi (Psychopharmacology, 2025)
Rationale Despite decades of research and medical development, relapse to drug seeking continues to be a significant challenge in the treatment of substance use disorders. GABA B receptor (GABA B -R) agonists have been shown preclinically to inhibit relapse by acting on midbrain dopamine (DA) neurons and are sometimes used off-label for the treatment of alcohol use disorder. Studies in rodent models show reduced GABA B -R signaling in DA neurons after exposure to stimulants. Similarly, our recent data demonstrated reduced GABA B -R currents in DA neurons during prolonged abstinence from fentanyl vapor self-administration (SA). However, the mechanism of opioid-induced changes in GABA B -R currents is not well understood. In addition, GABA B -R agonists are plagued with a plethora of side effects limiting their potential clinical use. Objectives In this study we aimed to answer the following questions: first, can we use GABA B -R positive allosteric modulators (PAMs) to inhibit relapse to opioid seeking? Secondly, how do opioids result in reduced GABA B -R signaling during prolonged abstinence? Approach To this end, we tested the effects of a novel GABA B -R PAM (KK-92A) on reinstatement of drug seeking in a rat model of intravenous (IV) fentanyl SA. Using in situ hybridization with RNAscope, we examined the effects of opioids on mRNA levels of various genes involved in GABA B -R signaling, in two rodent models of opioid addiction including a rat model of IV fentanyl SA and a mouse model of fentanyl vapor SA. Results Our results show that KK-92A inhibits relapse to fentanyl but not sucrose-seeking in rats, and fentanyl SA results in reduced mRNA levels of the G protein-coupled inwardly rectifying potassium channel subtypes 2 and 3 (GIRK 2/3 ). Conclusion These findings suggest that PAMs like KK-92A are a potential therapeutic strategy for opioid use disorder and their effect is likely due to rectifying GABA B -R mediated inhibition of midbrain DA neurons, which is reduced after opioid SA due to reduced GIRK 2/3 expression.

Morphological, biochemical, and molecular characterization of the root-knot nematode Meloidogyne spartinae and assessment of bacterial assemblages in infected smooth cordgrass roots - Janete A. Brito; Samuel J. Martins; Amy Michaud; Sergei A. Subbotin; Silvia Vau; Josephine M. Pasche; Ruimin Xue; Jason D. Stanley (Antonie van Leeuwenhoek, 2025)

Correction: Identifying remnant biodiversity hotspots in Southern Asia reveals disequilibrium in mammalian communities - Caroline Charão Sartor; Zaneta Kaszta; Jan Kamler; Andrew J. Hearn; Eric Ash; Gilmoore Bolongon; Özgün Emre Can; Phan Channa; Susan Cheyne; Amy Fitzmaurice; Iding Achmad Haidir; Pyae Phyoe Kyaw; et al. (Biodiversity and Conservation, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA) - Monita Sharma; Erin Huber; Emma Arnesdotter; Holger P. Behrsing; Adam Bettmann; David Brandwein; Samuel Constant; Rahul Date; Abhay Deshpande; Eric Fabian; Amit Gupta; Robert Gutierrez; et al. (Archives of Toxicology, 2025)
Standard information reporting helps to ensure that assay conditions and data are consistently reported and to facilitate inter-laboratory comparisons. Here, we present recommendations on minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA). The TEER assay is extensively used to evaluate the health of an epithelial/endothelial cell culture model and as an indicator of the potential toxicity of a test substance. This publication is the result of an international collaboration─called the RespTox (Respiratory Toxicity) Collaborative─through which twelve laboratories shared their protocols for assessing the barrier function of respiratory epithelial cells using the TEER assay following exposure to substances. The protocols from each laboratory were reviewed to identify general steps for performing the TEER assay, interlaboratory differences between steps, the rationale for differences, whether these differences impact results or cross-laboratory comparisons between TEER measurements. While the MIRTA recommendations are focused on respiratory epithelial cell systems, these recommendations can be adapted for other cell systems that form barriers. The use of these recommendations will support data transparency and reproducibility, reduce challenges in data interpretation, enable cross-laboratory comparisons, help assess study quality, and facilitate the incorporation of the TEER assay into national and international testing guidance.

From conflict to collaboration through inclusive landscape governance: Evidence from a contested landscape in Ghana - James Reed; Mirjam A.F. Ros-Tonen; Samuel Adeyanju; Abdul Wahid Arimiyaw; Kwabena Asubonteng; Bernard N. Baatuwie; Eric R.C. Bayala; Damian Tom-Dery; Amy Ickowitz; Yakubu B. Issaka; Kaala B. Moombe; Joseph Mumuni; et al. (Global Environmental Change, 2024)

Identifying remnant biodiversity hotspots in Southern Asia reveals disequilibrium in mammalian communities - Caroline Charão Sartor; Zaneta Kaszta; Jan Kamler; Andrew J. Hearn; Eric Ash; Gilmoore Bolongon; Özgün Emre Can; Phan Channa; Susan Cheyne; Amy Fitzmaurice; Iding Achmad Haidir; Pyae Phyoe Kyaw; et al. (Biodiversity and Conservation, 2024)
Identification of highly biodiverse areas has become a crucial step in protecting species richness, especially considering the rapid collapse of biodiversity and the limited funds available to avert, far less to reverse, these trends. Therefore, we aimed to identify the most important areas for the conservation of specified mammalian groups in Southern Asia, a region rich in biodiversity hotspots threatened by increasing rates of habitat loss and other anthropogenic activities. To achieve this, we modelled the occupancy of ungulates and of small, medium and large carnivorans at 20 study sites across the region and identified hotspots of species richness. We analysed the variation of estimated space use between different species groups and ranked areas according to their predicted importance for mammalian species conservation. Our results reveal a significant positive correlation in the spatial utilization patterns of competitive carnivores, yet no correlation among carnivores and their prey species, suggesting that anthropogenic impacts in the region are constraining species to coexist in only the few remaining suitable areas, superseding interactions between species guilds. Although the rank of site importance varied amongst species groups, we were able to identify a consensus on sites that are crucial for the conservation of all groups considered. Most of these top-ranking sites were located in the peninsular region of Thailand. We argue that, of the areas assessed, these sites represent the most important refuges for species conservation in the region, and their protection is critical for the maintenance of the biodiversity in Southern Asia.

Biogeographic variation in environmental and biotic resistance modifies predicted risk of marine invasions by ships - Mariana Bonfim; Samuel L. Bunson; Andrew J. Sellers; Mark E. Torchin; Gregory M. Ruiz; Amy L. Freestone (Frontiers in Marine Science, 2024)
Introduction Global shipping has accelerated the spread of non-native species. Factors such as environmental filtering and interactions with local biota can affect invasion likelihood, yet their relative contribution to predicting invasion risk remains unresolved. To test how abiotic filters and an experimentally-derived measure of biotic resistance interact with propagule pressure, we developed an integrated model to evaluate their relative effects on invasion risk of marine biofouling organisms to different focal port regions. We predicted that environmental filtering impacts invasion risk when fewer but stronger connections are part of the network. Further, predation is a mechanism of biotic resistance, which can reduce invasion risk, with most pronounced effects predicted in the tropics that decline at higher latitudes. Methods We examined shipping traffic and predation impact at three coastal bioregions spanning 47-degrees of latitude al range in the Northeast Pacific (Alaska, California, and Panama). We used vessel traffic databases to characterize propagule pressure and construct a worldwide port network of marine shipping routes and ports. Environmental resistance was estimated using temperature and salinity data from donor and recipient regions. We further used standardized predator exposure experiments to quantify predation impact on fouling community biomass as an estimate of potential for biotic resistance. We then expanded on existing models of relative invasion risk to incorporate the probability that propagules will survive predation by local predators and overcome environmental filtering to generate a predicted invasion risk for each port. Results Environmental filtering in all regions and predation pressure in the tropics worked to reduce the invasion risk, resulting in markedly different cumulative risk profiles over time among regions. Discussion In an increasingly connected world with more vessel traffic, our results highlight that while the number and distribution of shipping routes are important to understand risk, abiotic and biotic filters can modify model predictions.

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

Building capacity for climate adaptation planning in protected area management: Options and challenges for World Heritage - Jess Melbourne-Thomas; Brenda B. Lin; Mandy Hopkins; Rosemary Hill; Michael Dunlop; Nicholas MacGregor; Samuel D. Merson; Caitlin Vertigan; Luke Donegan; Marian Sheppard; Jacqui Meyers; Linda Thomas; et al. (Biological Conservation, 2024)

Near-Inertial Energy Variability in a Strong Mesoscale Eddy Field in the Iceland Basin - Gunnar Voet; Amy Waterhouse; Anna Savage; Eric Kunze; Jennifer MacKinnon; Matthew Alford; John Colosi; Harper Simmons; Thilo Klenz; Samuel Kelly; James Moum; Caitlin Whalen; et al. (Oceanography, 2024)
An 18-month deployment of moored sensors in Iceland Basin allows characterization of near-inertial (frequencies near the Coriolis frequency f with periods of ~14 h) internal gravity wave generation and propagation in a region with an active mesoscale eddy field and strong seasonal wind and heat forcing. The seasonal cycle in surface forcing deepens the mixed layer in winter and controls excitation of near-​inertial energy. The mesoscale eddy field modulates near-inertial wave temporal, horizontal, and vertical scales, as well as propagation out of the surface layer into the deep permanent pycnocline. Wind-forced near-inertial energy has the most active downward propagation within anticyclonic eddies. As oceanic surface and bottom boundaries act to naturally confine the propagation of internal waves, the vertical distribution of these waves can be decomposed into a set of “standing” vertical modes that each propagate horizontally at different speeds. The lowest modes, which propagate quickly away from their generation sites, are most enhanced when the mixed layer is deep and are generally directed southward.

Detecting the invasive Lespedeza cuneata in grasslands using commercial small satellite imagery - M. Ny Aina Rakotoarivony; Hamed Gholizadeh; William M. Hammond; Kianoosh Hassani; Omkar Joshi; Robert G. Hamilton; Samuel D. Fuhlendorf; Amy M. Trowbridge; Henry D. Adams (International Journal of Remote Sensing, 2023)

Seasonal development of a tidal mixing front drives shifts in community structure and diversity of bacterioplankton - Nathan G. King; Sophie‐B Wilmes; Samuel S. Browett; Amy Healey; Allan D. McDevitt; Niall J. McKeown; Ronan Roche; Ilze Skujina; Dan A. Smale; Jamie M. Thorpe; Shelagh Malham (Molecular Ecology, 2023)
Bacterioplankton underpin biogeochemical cycles and an improved understanding of the patterns and drivers of variability in their distribution is needed to determine their wider functioning and importance. Sharp environmental gradients and dispersal barriers associated with ocean fronts are emerging as key determinants of bacterioplankton biodiversity patterns. We examined how the development of the Celtic Sea Front (CF), a tidal mixing front on the Northwest European Shelf affects bacterioplankton communities. We performed 16S‐rRNA metabarcoding on 60 seawater samples collected from three depths (surface, 20 m and seafloor), across two research cruises (May and September 2018), encompassing the intra‐annual range of the CF intensity. Communities above the thermocline of stratified frontal waters were clearly differentiated and less diverse than those below the thermocline and communities in the well‐mixed waters of the Irish Sea. This effect was much more pronounced in September, when the CF was at its peak intensity. The stratified zone likely represents a stressful environment for bacterioplankton due to a combination of high temperatures and low nutrients, which fewer taxa can tolerate. Much of the observed variation was driven by Synechococcus spp. (cyanobacteria), which were more abundant within the stratified zone and are known to thrive in warm oligotrophic waters. Synechococcus spp. are key contributors to global primary productivity and carbon cycling and, as such, variability driven by the CF is likely to influence regional biogeochemical processes. However, further studies are required to explicitly link shifts in community structure to function and quantify their wider importance to pelagic ecosystems.

A holistic and comprehensive data approach validates the distribution of the critically endangered flapper skate ( Dipturus intermedius ) - Amy Garbett; Sophie L. Loca; Thomas Barreau; Manuel Biscoito; Caroline Bradley; Joe Breen; Maurice Clarke; Jim R. Ellis; Andrew M. Griffiths; Gary Hannon; Klara Jakobsdóttir; Claudia Junge; et al. (Journal of Fish Biology, 2023)
Morphological similarities between skates of the genus Dipturus in the north‐eastern Atlantic and Mediterranean have resulted in longstanding confusion, misidentification and misreporting. Current evidence indicates that the common skate is best explained as two species, the flapper skate ( Dipturus intermedius ) and the common blue skate ( D. batis ). However, some management and conservation initiatives developed prior to the separation continue to refer to common skate (as ‘ D. batis’ ). This taxonomic uncertainty can lead to errors in estimating population viability, distribution range, and impact on fisheries management and conservation status. Here, we demonstrate how a concerted taxonomic approach, using molecular data and a combination of survey, angler and fisheries data, in addition to expert witness statements, can be used to build a higher resolution picture of the current distribution of D. intermedius . Collated data indicate that flapper skate has a more constrained distribution compared to the perceived distribution of the ‘common skate’, with most observations recorded from Norway and the western and northern seaboards of Ireland and Scotland, with occasional specimens from Portugal and the Azores. Overall, the revised spatial distribution of D. intermedius has significantly reduced the extant range of the species, indicating a possibly fragmented distribution range.

Antibody Fc-binding profiles and ACE2 affinity to SARS-CoV-2 RBD variants - Ebene R. Haycroft; Samantha K. Davis; Pradhipa Ramanathan; Ester Lopez; Ruth A. Purcell; Li Lynn Tan; Phillip Pymm; Bruce D. Wines; P. Mark Hogarth; Adam K. Wheatley; Jennifer A. Juno; Samuel J. Redmond; et al. (Medical Microbiology and Immunology, 2023)
Emerging SARS-CoV-2 variants, notably Omicron, continue to remain a formidable challenge to worldwide public health. The SARS-CoV-2 receptor-binding domain (RBD) is a hotspot for mutations, reflecting its critical role at the ACE2 interface during viral entry. Here, we comprehensively investigated the impact of RBD mutations, including 5 variants of concern (VOC) or interest—including Omicron (BA.2)—and 33 common point mutations, both on IgG recognition and ACE2-binding inhibition, as well as FcγRIIa- and FcγRIIIa-binding antibodies, in plasma from two-dose BNT162b2-vaccine recipients and mild-COVID-19 convalescent subjects obtained during the first wave using a custom-designed bead-based 39-plex array. IgG-recognition and FcγR-binding antibodies were decreased against the RBD of Beta and Omicron, as well as point mutation G446S, found in several Omicron sub-variants as compared to wild type. Notably, while there was a profound decrease in ACE2 inhibition against Omicron, FcγR-binding antibodies were less affected, suggesting that Fc functional antibody responses may be better retained against the RBD of Omicron in comparison to neutralization. Furthermore, while measurement of RBD–ACE2-binding affinity via biolayer interferometry showed that all VOC RBDs have enhanced affinity to human ACE2, we demonstrate that human ACE2 polymorphisms, E35K (rs1348114695) has reduced affinity to VOCs, while K26R (rs4646116) and S19P (rs73635825) have increased binding kinetics to the RBD of VOCs, potentially affecting virus–host interaction and, thereby, host susceptibility. Collectively, our findings provide in-depth coverage of the impact of RBD mutations on key facets of host–virus interactions.

Effects of concurrent exercise training on body composition, systemic inflammation, and components of metabolic syndrome in inactive academics: a randomised controlled trial - Samuel M. Higham; Amy E. Mendham; Simon Rosenbaum; Nicholas G. Allen; Greg Smith; Antony Stadnyk; Rob Duffield (European Journal of Applied Physiology, 2023)

What makes a good life: using theatrical performance to enhance communication about polygenic risk scores research in patient and public involvement - Amy M. Mason; Ifunanya Obi; Olamide Ayodele; Samuel A. Lambert; Sarah Fahle (Journal of Community Genetics, 2023)
The aim of this patient and public involvement and engagement (PPIE) work was to explore improvised theatre as a tool for facilitating bi-directional dialogue between researchers and patients/members of the public on the topic of polygenic risk scores (PRS) use within primary or secondary care. PRS are a tool to quantify genetic risk for a heritable disease or trait and may be used to predict future health outcomes. In the United Kingdom (UK), they are often cited as a next-in-line public health tool to be implemented, and their use in consumer genetic testing as well as patient-facing settings is increasing. Despite their potential clinical utility, broader themes about how they might influence an individual’s perception of disease risk and decision-making are an active area of research; however, this has mostly been in the setting of return of results to patients. We worked with a youth theatre group and patients involved in a PPIE group to develop two short plays about public perceptions of genetic risk information that could be captured by PRS. These plays were shared in a workshop with patients/members of the public to facilitate discussions about PRS and their perceived benefits, concerns and emotional reactions. Discussions with both performers and patients/public raised three key questions: (1) can the data be trusted?; (2) does knowing genetic risk actually help the patient?; and (3) what makes a life worthwhile? Creating and watching fictional narratives helped all participants explore the potential use of PRS in a clinical setting, informing future research considerations and improving communication between the researchers and lay members of the PPIE group.

Country specific low carbon commitments versus equitable and practical company specific decarbonisation targets - Harmke Immink; Robbie Louw; Amy Garlick; Samuel Vosper; Alan Brent (Environment, Development and Sustainability, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The long and the short of it: Mechanisms of synchronous and compensatory dynamics across temporal scales - Lauren G. Shoemaker; Lauren M. Hallett; Lei Zhao; Daniel C. Reuman; Shaopeng Wang; Kathryn L. Cottingham; Richard J. Hobbs; Max C. N. Castorani; Amy L. Downing; Joan C. Dudney; Samuel B. Fey; Laureano A. Gherardi; et al. (Ecology, 2022)
Synchronous dynamics (fluctuations that occur in unison) are universal phenomena with widespread implications for ecological stability. Synchronous dynamics can amplify the destabilizing effect of environmental variability on ecosystem functions such as productivity, whereas the inverse, compensatory dynamics, can stabilize function. Here we combine simulation and empirical analyses to elucidate mechanisms that underlie patterns of synchronous versus compensatory dynamics. In both simulated and empirical communities, we show that synchronous and compensatory dynamics are not mutually exclusive but instead can vary by timescale. Our simulations identify multiple mechanisms that can generate timescale‐specific patterns, including different environmental drivers, diverse life histories, dispersal, and non‐stationary dynamics. We find that traditional metrics for quantifying synchronous dynamics are often biased toward long‐term drivers and may miss the importance of short‐term drivers. Our findings indicate key mechanisms to consider when assessing synchronous versus compensatory dynamics and our approach provides a pathway for disentangling these dynamics in natural systems.

Using kinematics to re-define the pull test as a quantitative biomarker of the postural response in normal pressure hydrocephalus patients - Samuel Daly; Jacob T. Hanson; Vibha Mavanji; Amy Gravely; James Jean; Alec Jonason; Scott Lewis; James Ashe; John M. Looft; Robert A. McGovern (Experimental Brain Research, 2022)

Fruit and seed traits of native and invasive plant species in Hawai‘i: implications for seed dispersal by non-native birds - Jinelle H. Sperry; Dylan O’Hearn; Donald R. Drake; Amy M. Hruska; Samuel B. Case; Jeferson Vizentin-Bugoni; Clint Arnett; Tim Chambers; Corey E. Tarwater (Biological Invasions, 2021)

Positive Social-Ecological Feedbacks in Community-Based Conservation - Anastasia C. E. Quintana; Alfredo Giron-Nava; Samuel Urmy; Alli N. Cramer; Santiago Domínguez-Sánchez; Salvador Rodríguez-Van Dyck; Octavio Aburto-Oropeza; Xavier Basurto; Amy Hudson Weaver (Frontiers in Marine Science, 2021)
Marine area-based conservation measures including no-take zones (areas with no fishing allowed) are often designed through lengthy processes that aim to optimize for ecological and social objectives. Their (semi) permanence generates high stakes in what seems like a one-shot game. In this paper, we theoretically and empirically explore a model of short-term area-based conservation that prioritizes adaptive co-management: temporary areas closed to fishing, designed by the fishers they affect, approved by the government, and adapted every 5 years. In this model, no-take zones are adapted through learning and trust-building between fishers and government fisheries scientists. We use integrated social-ecological theory and a case study of a network of such fisheries closures (“fishing refugia”) in northwest Mexico to hypothesize a feedback loop between trust, design, and ecological outcomes. We argue that, with temporary and adaptive area-based management, social and ecological outcomes can be mutually reinforcing as long as initial designs are ecologically “good enough” and supported in the social-ecological context. This type of adaptive management also has the potential to adapt to climate change and other social-ecological changes. This feedback loop also predicts the dangerous possibility that low trust among stakeholders may lead to poor design, lack of ecological benefits, eroding confidence in the tool’s capacity, shrinking size, and even lower likelihood of social-ecological benefits. In our case, however, this did not occur, despite poor ecological design of some areas, likely due to buffering by social network effects and alternative benefits. We discuss both the potential and the danger of temporary area-based conservation measures as a learning tool for adaptive co-management and commoning.

Historical patterns in mercury exposure for North American songbirds - Marie Perkins; Oksana P. Lane; David C. Evers; Amy Sauer; Evan M. Adams; Nelson J. O’Driscoll; Samuel T. Edmunds; Allyson K. Jackson; Julie C. Hagelin; Jeremiah Trimble; Elsie M. Sunderland (Ecotoxicology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The role of hybridization during ecological divergence of southwestern white pine ( Pinus strobiformis ) and limber pine ( P. flexilis ) - Mitra Menon; Justin C. Bagley; Christopher J. Friedline; Amy V. Whipple; Anna W. Schoettle; Alejandro Leal‐Sàenz; Christian Wehenkel; Francisco Molina‐Freaner; Lluvia Flores‐Rentería; M. Socorro Gonzalez‐Elizondo; Richard A. Sniezko; Samuel A. Cushman; et al. (Molecular Ecology, 2018)
Interactions between extrinsic factors, such as disruptive selection and intrinsic factors, such as genetic incompatibilities among loci, often contribute to the maintenance of species boundaries. The relative roles of these factors in the establishment of reproductive isolation can be examined using species pairs characterized by gene flow throughout their divergence history. We investigated the process of speciation and the maintenance of species boundaries between Pinus strobiformis and Pinus flexilis . Utilizing ecological niche modelling, demographic modelling and genomic cline analyses, we illustrated a divergence history with continuous gene flow. Our results supported an abundance of advanced generation hybrids and a lack of loci exhibiting steep transition in allele frequency across the hybrid zone. Additionally, we found evidence for climate‐associated variation in the hybrid index and niche divergence between parental species and the hybrid zone. These results are consistent with extrinsic factors, such as climate, being an important isolating mechanism. A build‐up of intrinsic incompatibilities and of coadapted gene complexes is also apparent, although these appear to be in the earliest stages of development. This supports previous work in coniferous species demonstrating the importance of extrinsic factors in facilitating speciation. Overall, our findings lend support to the hypothesis that varying strength and direction of selection pressures across the long lifespans of conifers, in combination with their other life history traits, delays the evolution of strong intrinsic incompatibilities.

A Dose Ranging Pharmacokinetic Evaluation of IQP-0528 Released from Intravaginal Rings in Non-Human Primates - Jonathan T. Su; Ryan S. Teller; Priya Srinivasan; Jining Zhang; Amy Martin; Samuel Sung; James M. Smith; Patrick F. Kiser (Pharmaceutical Research, 2017)

Inhalation of gas metal arc–stainless steel welding fume promotes lung tumorigenesis in A/J mice - Lauryn M. Falcone; Aaron Erdely; Terence G. Meighan; Lori A. Battelli; Rebecca Salmen; Walter McKinney; Samuel Stone; Amy Cumpston; Jared Cumpston; Ronnee N. Andrews; Michael Kashon; James M. Antonini; et al. (Archives of Toxicology, 2017)

The effect of high-intensity aerobic interval training on markers of systemic inflammation in sedentary populations - Nicholas G. Allen; Samuel M. Higham; Amy E. Mendham; Tegan E. Kastelein; Penelope S. Larsen; Rob Duffield (European Journal of Applied Physiology, 2017)

Inferring infection hazard in wildlife populations by linking data across individual and population scales - Kim M. Pepin; Shannon L. Kay; Ben D. Golas; Susan S. Shriner; Amy T. Gilbert; Ryan S. Miller; Andrea L. Graham; Steven Riley; Paul C. Cross; Michael D. Samuel; Mevin B. Hooten; Jennifer A. Hoeting; et al. (Ecology Letters, 2017)
Our ability to infer unobservable disease‐dynamic processes such as force of infection (infection hazard for susceptible hosts) has transformed our understanding of disease transmission mechanisms and capacity to predict disease dynamics. Conventional methods for inferring FOI estimate a time‐averaged value and are based on population‐level processes. Because many pathogens exhibit epidemic cycling and FOI is the result of processes acting across the scales of individuals and populations, a flexible framework that extends to epidemic dynamics and links within‐host processes to FOI is needed. Specifically, within‐host antibody kinetics in wildlife hosts can be short‐lived and produce patterns that are repeatable across individuals, suggesting individual‐level antibody concentrations could be used to infer time since infection and hence FOI . Using simulations and case studies (influenza A in lesser snow geese and Yersinia pestis in coyotes), we argue that with careful experimental and surveillance design, the population‐level FOI signal can be recovered from individual‐level antibody kinetics, despite substantial individual‐level variation. In addition to improving inference, the cross‐scale quantitative antibody approach we describe can reveal insights into drivers of individual‐based variation in disease response, and the role of poorly understood processes such as secondary infections, in population‐level dynamics of disease.

Proof-of-Concept of Polymeric Sol-Gels in Multi-Drug Delivery and Intraoperative Image-Guided Surgery for Peritoneal Ovarian Cancer - Matthew McKenzie; David Betts; Amy Suh; Kathryn Bui; Rui Tang; Kexian Liang; Samuel Achilefu; Glen S. Kwon; Hyunah Cho (Pharmaceutical Research, 2016)

A comparative approach to assess drivers of success in mammalian conservation recovery programs - Jennifer J. Crees; Amy C. Collins; P. J. Stephenson; Helen M. R. Meredith; Richard P. Young; Caroline Howe; Mark R. Stanley Price; Samuel T. Turvey (Conservation Biology, 2016)
The outcomes of species recovery programs have been mixed; high‐profile population recoveries contrast with species‐level extinctions. Each conservation intervention has its own challenges, but to inform more effective management it is imperative to assess whether correlates of wider recovery program success or failure can be identified. To contribute to evidence‐based improvement of future conservation strategies, we conducted a global quantitative analysis of 48 mammalian recovery programs. We reviewed available scientific literature and conducted semistructured interviews with conservation professionals involved in different recovery programs to investigate ecological, management, and political factors associated with population recoveries or declines. Identifying and removing threats was significantly associated with increasing population trend and decreasing conservation dependence, emphasizing that populations are likely to continue to be compromised in the absence of effective threat mitigation and supporting the need for threat monitoring and adaptive management in response to new and potential threats. Lack of habitat and small population size were cited as limiting factors in 56% and 42% of recovery programs, respectively, and both were statistically associated with increased longer term dependence on conservation intervention, demonstrating the importance of increasing population numbers quickly and restoring and protecting habitat. Poor stakeholder coordination and management were also regularly cited by respondents as key weaknesses in recovery programs, indicating the importance of effective leadership and shared goals and management plans. Project outcomes were not influenced by biological or ecological variables such as body mass or habitat, which suggests that these insights into correlates of conservation success and failure are likely to be generalizable across mammals.

Shifts in microbial food web structure and productivity after additions of naturally occurring dissolved organic matter: Results from large‐scale lacustrine mesocosms - Robert W. Sanders; Sandra L. Cooke; Janet M. Fischer; Samuel B. Fey; Adam W. Heinze; Wade H. Jeffrey; Amy L. Macaluso; Robert E. Moeller; Donald P. Morris; Patrick J. Neale; Mark H. Olson; J. Dean Pakulski; et al. (Limnology and Oceanography, 2015)
Predicting the effects of dissolved organic matter (DOM) on pelagic food webs can be difficult because DOM modifies water column optics and can have contrasting effects on species across trophic levels. We combined large mesocosm, smaller‐scale experiments and autoregressive modeling driven bu DOC concentration or DOM optical quality (colored DOM, or CDOM, measured as DOC‐specific absorbance at 320 nm, SUVA 320 ) to assess how heterotrophic and phototrophic microbial populations were altered in a temperate oligotrophic lake. DOM additions yielded DOC concentrations of 1.6 mg L −1 (control) 2.5 mg L −1 , 3.0 mg L −1 , and 4.3 mg L −1 . Primary (PP) and bacterial (BP) production as well as heterotrophic and autotrophic protist abundances were stimulated in the higher DOM additions. BP responded rapidly to DOM additions, but unlike PP, returned to the level of controls within 2–7 d. A bioassay showed that the DOM was a nitrogen source for phytoplankton. The two models revealed that BP and edible phytoplankton were stimulated by CDOM (SUVA 320 ), but only BP was stimulated by DOC concentration. Ultraviolet radiation (UV) inhibited protists in both models, but stimulated edible phytoplankton only in the SUVA 320 model runs. These results suggest that in transparent oligotrophic lakes large influxes of terrestrial (high SUVA 320 ) DOM will stimulate the microbial food web by providing a nutrient subsidy to bacteria and reducing exposure of protists to damaging UV. Nutrients associated with moderate DOM input may also stimulate PP relative to BP, as was observed in these and other experiments, rather than causing an overall system shift toward heterotrophy.

Songbirds as sentinels of mercury in terrestrial habitats of eastern North America - Allyson K. Jackson; David C. Evers; Evan M. Adams; Daniel A. Cristol; Collin Eagles-Smith; Samuel T. Edmonds; Carrie E. Gray; Bart Hoskins; Oksana P. Lane; Amy Sauer; Timothy Tear (Ecotoxicology, 2015)

The under‐ice microbiome of seasonally frozen lakes - Stefan Bertilsson; Amy Burgin; Cayelan C. Carey; Samuel B. Fey; Hans-Peter Grossart; Lorena M. Grubisic; Ian D. Jones; Georgiy Kirillin; Jay T. Lennon; Ashley Shade; Robyn L. Smyth (Limnology and Oceanography, 2013)
Compared to the well‐studied open water of the “growing” season, under‐ice conditions in lakes are characterized by low and rather constant temperature, slow water movements, limited light availability, and reduced exchange with the surrounding landscape. These conditions interact with ice‐cover duration to shape microbial processes in temperate lakes and ultimately influence the phenology of community and ecosystem processes. We review the current knowledge on microorganisms in seasonally frozen lakes. Specifically, we highlight how under‐ice conditions alter lake physics and the ways that this can affect the distribution and metabolism of auto‐ and heterotrophic microorganisms. We identify functional traits that we hypothesize are important for understanding under‐ice dynamics and discuss how these traits influence species interactions. As ice coverage duration has already been seen to reduce as air temperatures have warmed, the dynamics of the under‐ice microbiome are important for understanding and predicting the dynamics and functioning of seasonally frozen lakes in the near future.

Thermal tolerance of larvae of Pollicipes elegans, a marine species with an antitropical distribution - Kathleen Walther; Samuel E. Crickenberger; Sergio Marchant; Peter B. Marko; Amy L. Moran (Marine Biology, 2013)

A live weight–heart girth relationship for accurate dosing of east African shorthorn zebu cattle - Maia Lesosky; Sarah Dumas; Ilana Conradie; Ian Graham Handel; Amy Jennings; Samuel Thumbi; Phillip Toye; Barend Mark de Clare Bronsvoort (Tropical Animal Health and Production, 2012)

Antagonism at NMDA receptors, but not β-adrenergic receptors, disrupts the reconsolidation of pavlovian conditioned approach and instrumental transfer for ethanol-associated conditioned stimuli - Amy L. Milton; Moritz J. W. Schramm; James R. Wawrzynski; Felicity Gore; Faye Oikonomou-Mpegeti; Nancy Q. Wang; Daniel Samuel; Daina Economidou; Barry J. Everitt (Psychopharmacology, 2012)

Erratum to: Diethylene Glycol in Health Products Sold Over-the-Counter and Imported from Asian Countries - Joshua G. Schier; Dana B. Barr; Zheng Li; Amy F. Wolkin; Samuel E. Baker; Lauren S. Lewis; Michael A. McGeehin (Journal of Medical Toxicology, 2011)

Diethylene Glycol in Health Products Sold Over-the-Counter and Imported from Asian Countries - Joshua G. Schier; Dana B. Barr; Zheng Li; Amy F. Wolkin; Samuel E. Baker; Lauren S. Lewis; Michael A. McGeehin (Journal of Medical Toxicology, 2011)

Cyanonectria, a new genus for Nectria cyanostoma and its Fusarium anamorph - Gary J. Samuels; Bing-sheng Lu; Priscila Chaverri; Françoise Candoussau; Jacques Fournier; Amy Y. Rossman (Mycological Progress, 2009)

Decline in Relative Abundance of Bottlenose Dolphins Exposed to Long‐Term Disturbance - LARS BEJDER; AMY SAMUELS; HAL WHITEHEAD; NICK GALES; JANET MANN; RICHARD CONNOR; MIKE HEITHAUS; JANA WATSON‐CAPPS; CINDY FLAHERTY; MICHAEL KRÜTZEN (Conservation Biology, 2006)
Studies evaluating effects of human activity on wildlife typically emphasize short‐term behavioral responses from which it is difficult to infer biological significance or formulate plans to mitigate harmful impacts. Based on decades of detailed behavioral records, we evaluated long‐term impacts of vessel activity on bottlenose dolphins ( Tursiops sp.) in Shark Bay, Australia. We compared dolphin abundance within adjacent 36‐km 2 tourism and control sites, over three consecutive 4.5‐year periods wherein research activity was relatively constant but tourism levels increased from zero, to one, to two dolphin‐watching operators. A nonlinear logistic model demonstrated that there was no difference in dolphin abundance between periods with no tourism and periods in which one operator offered tours. As the number of tour operators increased to two, there was a significant average decline in dolphin abundance (14.9%; 95% CI =−20.8 to −8.23), approximating a decline of one per seven individuals. Concurrently, within the control site, the average increase in dolphin abundance was not significant (8.5%; 95% CI =−4.0 to +16.7). Given the substantially greater presence and proximity of tour vessels to dolphins relative to research vessels, tour‐vessel activity contributed more to declining dolphin numbers within the tourism site than research vessels. Although this trend may not jeopardize the large, genetically diverse dolphin population of Shark Bay, the decline is unlikely to be sustainable for local dolphin tourism. A similar decline would be devastating for small, closed, resident, or endangered cetacean populations. The substantial effect of tour vessels on dolphin abundance in a region of low‐level tourism calls into question the presumption that dolphin‐watching tourism is benign.

Tissue distribution of cholinesterases and anticholinesterases in native and transgenic tomato plants - Samuel Fletcher; Brian Geyer; Amy Smith; Tama Evron; Lokesh Joshi; Hermona Soreq; Tsafrir Mor (Plant Molecular Biology, 2004)

SPERM WHALE DIVES TRACKED BY RADIO TAG TELEMETRY - William A. Watkins; Mary Ann Daher; Nancy A. Dimarzio; Amy Samuels; Douglas Wartzok; Kurt M. Fristrup; Paul W. Howey; Romaine R. Maiefski (Marine Mammal Science, 2002)
A bstract Dives of a 12‐m sperm whale ( Physeter catodon Linnaeus, 1758) were tracked in the southeast Caribbean by long range, 30 MHz radio tag with dive‐profile telemetry over 4.6 d, 26 April‐1 May 1995. Over the 295‐km track, average speed was 0.7 m/sec (2.6 km/h). Of 158 dives (defined as submergences longer than 3 min), 65 were shallow (

SPERM WHALE SURFACE ACTIVITY FROM TRACKING BY RADIO AND SATELLITE TAGS 1 - William A. Watkins; Mary Ann Daher; Nancy A. Dimarzio; Amy Samuels; Douglas Wartzok; Kurt M. Fristrup; Damon P. Gannon; Paul W. Howey; Romaine R. Maiefski; Trevor R. Spradlin (Marine Mammal Science, 1999)
A bstract Three 12‐m sperm whales ( Physeter catodon ) were tagged and tracked west of Dominica in the southeast Caribbean to follow the surfacing patterns and movements of these presumed subadult males. Whale N was tagged in April 1993 with a 30‐MHz radio tag and tracked for two days. Whale H was tagged in April 1995 with a 30‐MHz radio tag and tracked for 4.6 d. Whale A was tagged in April 1995 with a satellite‐monitored tag tracked by ARGOS for 21.5 d, the first four of which were concurrent with the tracking of Whale H, an associate. The tagged whales remained west of Dominica for at least 2, 5, and 13 d, respectively. Whales N and A then moved southward to waters off Martinique. There were no apparent effects on the whales by tagging or the presence of the tags. The whales averaged speeds of 2.6‐3.5 km/h. Surfacings, indicated by tag signals, were of two types: short surfacings apparently primarily for respiration, averaging 7‐10.5 min between repeated longer dives, occurring day and night; and extended surfacings seemingly for rest and social interactions with conspecifics, occurring mostly in daylight. Whales were near the surface for 20.4%–22.6% of the total time (26.6%–27.1% during the day and 14.9%–17.1% at night). Delayed blowing was observed as Whale N surfaced for 8.3 min between 47‐ and 45‐min dives but delayed the first of its 31 blows for 1.5 min after surfacing.

A QUANTITATIVE ASSESSMENT OF DOMINANCE RELATIONS AMONG BOTTLENOSE DOLPHINS - Amy Samuels; Tara Gifford (Marine Mammal Science, 1997)
A bstract Agonistic behavior of bottlenose dolphins was studied at Brookfield Zoo for nearly 4.5 yr, and dominance relationships were determined using a quantitative technique adapted from primate behavioral research. Dominance relations among dolphins were influenced by the gender of participants. Male dolphins were clearly and consistently dominant to females, and intersexual agonism occurred at moderate rates with seasonal peaks in spring and fall. Dominance relationships among female dolphins were age‐ordered and stable, even though agonism among females did occur at uniformly low rates. In contrast, the two males had a changeable dominance relationship in which periods of stability and low‐level agonism were interspersed with episodes of intense competition. Zoo‐based research revealed patterns of behavior that conformed to current knowledge about bottlenose dolphin social structure. Moreover, research in a zoo setting facilitated development of a quantitative technique that can be used to assess cetacean dominance relationships in field research.

Costs of maternal care: infant-carrying in baboons - Jeanne Altmann; Amy Samuels (Behavioral Ecology and Sociobiology, 1992)